Prospects for the accelerated improvement of the resilient crop quinoa. (18th June 2020) - López-Marqués, Rosa L; Nørrevang, Anton F; Ache, Peter; Moog, Max; Visintainer, Davide; Wendt, Toni; Østerberg, Jeppe T; Dockter, Christoph; Jørgensen, Morten E; Salvador, Andrés Torres; Hedrich, Rainer; Gao, Caixia; et al.
Abstract : Climate change is challenging food production worldwide. We propose a strategy to accelerate the improvement of a nutritious resilient crop to meet the future food production demands in a changing climate. Abstract: Crops tolerant to drought and salt stress may be developed by two approaches. First, major crops may be improved by introducing genes from tolerant plants. For example, many major crops have wild relatives that are more tolerant to drought and high salinity than the cultivated crops, and, once deciphered, the underlying resilience mechanisms could be genetically manipulated to produce crops with improved tolerance. Secondly, some minor (orphan) crops cultivated in marginal areas are already drought and salt tolerant. Improving the agronomic performance of these crops may be an effective way to increase crop and food diversity, and an alternative to engineering tolerance in major crops. Quinoa ( Chenopodium quinoa Willd.), a nutritious minor crop that tolerates drought and salinity better than most other crops, is an ideal candidate for both of these approaches. Although quinoa has yet to reach its potential as a fully domesticated crop, breeding efforts to improve the plant have been limited. Molecular and genetic techniques combined with traditional breeding are likely to change this picture. Here we analyse protein-coding sequences in the quinoa genome that are orthologous to domestication genes in established crops. Mutating only a limited number of such genes by targeted mutagenesis appears to be a promising route for accelerating the improvement of quinoa and generating a nutritious high-yielding crop that can meet the future demand for food production in a changing climate.